The Promotion of Values in Young People in Different Contexts of Sports Practice - Gema Ortega; José Robles; Manuel Tomás Abad; Luis Javier Durán; Ana Concepción Jiménez; Fco. Javier Giménez, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The educational potential of sport is a wide-ly researched topic area in sports science. This potential is greater or lesser depending on the focus given to sports. The objectives of this study are to: (i) Establish the reference values and their hierarchy in participants in the RMF’s Socio-sporting Basketball Schools compared with secondary school students; (ii) Identify whether there are differences according to sex and age group; (iii) To determine if there are differences in the relationships between dimensions comparing the RMF athletes and the group of secondary school students. The study includes 304 participants. Of these, 80 have engaged in sports at the RMF’s Socio-sporting Basketball Schools and 224 are secondary school students who had not played sports in the RMF’s schools. All participants are aged between 12 and 16 (M = 13.94; SD = 1.35). The instrument used is the Questionnaire on Values in Team Sports, in Spanish Cuestionario sobre Valores en los Deportes de Equipo (CUVADE) (12-16 years). This tool allows the researcher to establish the reference values of participants in team sports as well as the hierarchy in which they place these values, both inside and outside the educational and/or sports club setting. The athletes at the RMF Socio-sporting Schools exhibit a greater appreciation of the dimensions of sportsmanship, fair play, and peaceful behaviour. In addition, the boys and girls who play basketball at the RMF Socio-sporting Schools do not display significant differences in any of the six dimensions. However, the secondary school students display differences in the dimensions of personal and team success. According to the data obtained, the sporting-educational model of the RMF can be regarded as contributing to young athletes’ optimal personal development.